PENGEMBANGAN E-LKPD MENGIDENTIFIKASI ISI TEKS CERITA INSPIRATIF MELALUI DISCOVERY LEARNING UNTUK SISWA KELAS IX SMP - Fisnia Pratami; Sugiarti Sugiarti (Universitas Batanghari, 2022)
Learning in schools in the era of technological development is always related to teaching materials such as electronic student worksheets. The development of electronic student worksheets is the problem in this article. The purpose of this article is to describe the process of developing electronic student worksheets to identify the contents of inspirational story texts using the discovery learning model. This research and development uses the ADDIE model which is limited only to the development stage. The development stages include: analysis of existing needs in schools, designing products according to needs, product development and testing to validators, and improvements according to suggestions. Based on the assessment by media expert Mr. Uli Rizki, M.Kom., expert practitioner Mrs. Prillia Ekaningtiass, M.Pd., and material expert Mr. Andi Widiono, M.Pd. electronic student worksheets has been produced to identify the contents of inspirational story texts based on discovery learning learning models that are worthy of being tested for class IX students. The E-LKPD contains a cover/title page, an introductory page (description of the electronic student worksheets, study instructions, electronic student worksheets systematics, description of core competence, basic competencies, indicators, table of contents, materials, examples of inspiring story texts, exercises, evaluations, reflections, glossary, bibliography, and back cover.